Role of β-cd Macromolecule Anchored to α-fe2o3/tio2on the Selectivity and Partial Oxidation of Guaiacol to Add-Value Products - Salazar-Gonzalez, R (American Chemical Society, 2021)
Biomass is a naturally abundant, sustainable, and clean resource, which has the potential to replace fossil feedstock for sustainable production of high add-value chemicals. However, an efficient conversion process is still difficult to achieve due to the difficult reaction conditions. In this study as a novel and versatile concept, we introduced the use of β-cyclodextrin (β-CD) macromolecule to enhance the photocatalytic behavior of a α-Fe2O3/TiO2 heterojunction. The selective conversion of guaiacol was evaluated using 0.2, 1.0, and 2.0 molar ratios of β-CD anchored on 0.7 wt % α-Fe2O3/TiO2 under mild reaction conditions. 1.0 molar ratio of β-CD promoted photo-oxidation of guaiacol to mainly produce p-benzoquinone with ∼68% selectivity at ∼10% conversion. To understand this effect, Electron Paramagnetic Resonance Spectroscopy (EPR) in operando mode and Diffuse Reflectance Spectroscopy (DRS) experiments were performed. The results showed that the 1.0 molar ratio of β-CD decreases the bandgap from 3.06 to 2.76 eV and controls the •OH radical concentration due to the formation of a covalent bond between β-CD and semiconductors. The improved guaiacol adsorption capacity on the photocatalyst resulted in the enhancement of the photochemical activity and selectivity. Additionally, a possible pathway of guaiacol transformation was proposed through the oxidation intermediates. Furthermore, the photocatalyst β-CD/α-Fe2O3/TiO2 can be recycled efficiently and reused three times, without loss in reactivity. © 2021 American Chemical Society.
Keywords: guaiacol; lignocellulosic biomass; selective oxidation; heterogeneous photocatalysis; add-value products